Analisa Kinerja Lift Gedung D Kampus 1 Universitas Bina Bangsa Serang - Bambang Setyo Panulisan; Dedy Khaerudin; Asih Setyo Rini (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Rectorate's field of function is the function of improving performance, safety and efficiency in the use of elevators where the vertical transportation system is used as a tool to facilitate the activities of people and goods to move between certain floors in a building. Elevators are used as a tool to facilitate the activities of both people and goods to get to the floors In certain office and lecture buildings, it is a one-story building in building D which uses an elevator as a means of vertical lift transportation. Effective and efficient elevator planning is needed so that the elevator can be operated optimally. This should have a big impact on the comfort of building occupants as elevator users. One of the consequences of inadequate elevator planning is the occurrence of queues during peak hours. Therefore, some analysis of elevators in lecture and office buildings is needed. Elevator efficiency can be analyzed by calculating elevator requirements which depend on several variables such as lifting speed, lifting capacity, elevator waiting time, number of building occupants, and how large the building is. Meanwhile, the effectiveness of the lift can be obtained from the scheduling preparation and budget requirements involved in each lift's preventive maintenance. The research methodology used in this research is interviews, observation, secondary data collection, and data processing. From the results of data processing it can be concluded that the efficiency and effectiveness of the lift is 75% of the lift requirements for the 2 lift units provided. The research results also show several preventive maintenance schedules and preventive maintenance budgets within a one-year budget period.